Tongnaab: The History of a West African God - Allman, Jean; Parker, John (Indiana University Press, 2005)
For many Africanist historians, traditional religion is simply a starting point for measuring the historic impact of Christianity and Islam. In Tongnaab, Jean Allman and John Parker challenge the distinction between tradition and modernity by tracing the movement and mutation of the powerful Talensi god and ancestor shrine, Tongnaab, from the savanna of northern Ghana through the forests and coastal plains of the south. Using a wide range of written, oral, and iconographic sources, Allman and Parker uncover the historical dynamics of cross-cultural religious belief and practice. They reveal how Tongnaab has been intertwined with many themes and events in West African history – the slave trade, colonial conquest and rule, capitalist agriculture and mining, labor migration, shifting ethnicities, the production of ethnographic knowledge, and the political projects that brought about the modern nation state. This rich and original book shows that indigenous religion has been at the center of dramatic social and economic changes stretching from the slave trade to the tourist trade.
free
Keywords: History / Africa / West; Religion / Indigenous; Folk & Tribal